Peran Coretax Dalam Meningkatkan Kepatuhan Pengusaha Kena Pajak (PKP) Terhadap Kewajiban Pelaporan PPN (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of the Coretax system in improving the compliance of Taxable Entrepreneurs with the obligation to report Value Added Tax (VAT). Coretax is an information technology-based tax administration system designed to modernize and simplify the process of tax registration, payment, and reporting. The study used a qualitative approach with a case study method for PKP in the Ponorogo area, based on field observations and interviews with the Tax Consultant Office. The results of the study showed that Coretax improved timeliness, ease of use, and accuracy and completeness of data in VAT reporting. However, several obstacles were also found, such as limited internet infrastructure, lack of training, and technical obstacles in the system. To overcome these obstacles, PKP took advantage of assistance from Account Representatives (AR) at the KPP and tax consultant services. Overall, Coretax contributed positively to improving PKP compliance, although additional efforts were still needed to optimize its implementation throughout the region.